Evaluation of The Implementation of Fe Tablets for Adolescent Girl in 2019 at Pekanbaru City - Fathia Maulida (Universitas Airlangga, 2021)
Background: The program for giving Fe tablets is one of the efforts to overcome anemia based on WHO recommendations, one of the targets is the adolescent girl. Indicators of the success of this program are decreasing the incidence of anemia in adolescent girls and increasing adherence to iron tablets consumption.